Comparing convivialities: Dreams and realities of living-with-difference. (August 2014) - Nowicka, Magdalena; Vertovec, Steven
Conviviality across a number of disciplines now conveys a deeper concern with the human condition and how we think about human modes of togetherness. This collection of essays illustrates some of the ways conviviality can be used as an analytical tool to ask and explore the ways and conditions for living together. This introduction surveys a number of key ideas and meanings of 'conviviality' across various disciplines providing the readers with an overview of usages and understandings of the term. It identifies gaps in the existing literature, proposes how a comparative perspective elucidates the concepts and shows how the articles within this Special Issue contribute analytically to our understanding of conviviality.